PENTINGNYA STRATEGI MANAJEMEN PEMBIAYAAN DALAM MENINGKATKAN MUTU PENDIDIKAN (STUDI KASUS DI SMA NEGERI 1 BANYUKE HULU) - Larasanti, Julia; Wicaksono, Luhur; Salam, Urai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the financial management strategies implemented in schools to improve the quality of education and what activities are prioritized to be funded to improve the quality of education at SMA Negeri 1 Banyuke Hulu. The form of this research is qualitative research using case studies. Seven research participants consisting of the principal, deputy head of curriculum, treasurer, teachers, administration, school committee and school supervisor are the main data sources in this study. Data collection was done through interview, observation, documentation and focused discussion. Data analysis used qualitative descriptive method. The main findings of the analysis show that To improve the quality of education in SMA Negeri 1 Banyuke Hulu, a strategy for planning, implementing and evaluating education funding based on the principle of accountability is needed; Priority activities in SMA Negeri 1 Banyuke Hulu are developing teacher competence through training, improving infrastructure or educational facilities, and infrastructure and extracurricular scouting because it can help shape students' character, skills and spirituality; Based on the results of the research, the obstacle of the school is that it cannot collect, on the other hand, the funds owned are limited, which causes difficulties in developing school programs, while many programs must be financed with the funds owned by the school. This means that schools have to find other sources of funding for activities that are not included in the RKAS budget. The conclusion of this research is that SMA Negeri 1 Banyuke Hulu has shown a good financial management strategy to improve the quality of education. The implication of this research is that there is a need for continuous evaluation to ensure that prioritized activities can be carried out properly and can have an impact on improving the quality of education